Black silent majority : the Rockefeller drug laws and the politics of punishment - Fortner, Michael Javen, 1979- (Harvard University Press, 2015)
"Often seen as a political sop to the racial fears of white voters, aggressive policing and draconian sentencing for illegal drug possession and related crimes have led to the imprisonment of millions of African Americans--far in excess of their representation in the population as a whole. Michael Javen Fortner [argues] that these punitive policies also enjoyed the support of many working-class and middle-class blacks, who were angry about decline and disorder in their communities. [His book examines] the role African Americans played in creating today's system of mass incarceration"--Dust jacket flap